Impact and implementation of Healthy Life Centres, a primary-care service intervention for behaviour change in Norway: Study design. Issue 6 (August 2020) - Blom, Ellen Eimhjellen; Oldervoll, Line; Aadland, Eivind; Solbraa, Ane Kristiansen; Skrove, Guri Kaurstad
Aims: This ongoing study is investigating the implementation and long-term impact of Healthy Life Centres (HLCs), a primary-care service intervention for behaviour change in Norway. The primary aim is to study changes in objectively measured physical activity (PA) levels following a HLC intervention in the short (three months) and long term (15 months). Furthermore, the study is evaluating determinants concerning implementation and adaption of the HLC intervention that influence reach and impact on participants outcomes. Methods : This prospective observational study includes 32 HLCs from four different geographical regions in Norway. Subjects aged ⩾18 years were invited to participate. The study has a pre–post design with a 15-month follow-up. The HLC intervention is a three-month individualised program, containing personal consultations and group-based behaviour-specific courses on PA, diet and smoking cessation. Data collection consists of registration of objectively measured PA level, physical examinations, interviews and questionnaires. In addition, HLC organisation, offers, professions and resources are being examined. The Reach, Efficacy/Effectiveness, Adoption, Implementation and Maintenance (RE-AIM) framework is being applied to study the external validation of the HLC intervention. The study enrolled 1020 participants who gave their written informed consent. Post-tests and follow-up data collection is still ongoing and will continue until August 2019. Conclusions : By exploring the HLC intervention in a real-world setting and addressing the elements of RE-AIM, this study will contribute to an improved understanding and development of effective primary-care behaviour interventions such as the HLC model. The strengths of the study are the large sample size and the many HLCs and regions included.